2019
DOI: 10.1016/j.atherosclerosis.2019.04.217
|View full text |Cite
|
Sign up to set email alerts
|

CD39 identifies a microenvironment-specific anti-inflammatory CD8+ T-cell population in atherosclerotic lesions

Abstract: • CD8 + T-cells in atherosclerotic lesions show impaired IFN-γ and TNF-α production, associated with expression of CD39. • TCR signaling is required for the upregulation of CD39 + on lesional CD8 + T-cells. • Pharmacological inhibition of CD39 partly restores cytokine production of CD8 + T-cells in the atherosclerotic lesions. • CD8 + T-cells from human lesions display increased expression of CD39 compared to their circulating counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
0
15
1
1
Order By: Relevance
“…This could indicate that not the cytotoxic but the more quiescent CD8 + T-cell subsets are responding to plaque-specific antigens and may be more relevant in the pathogenesis of atherosclerosis. Using experimental mouse models of atherosclerosis it has been shown that the majority of CD8 + T cells in the plaque are antigen-specific, 38 but so far little is known regarding the plaque-antigen(s) they respond to. Whereas CD4 + T cells have been shown to respond to (ox)LDL ([oxidized] low-density lipoprotein) and its related apo B 100 peptide, plaque-antigen(s) for CD8 + remain mostly indefinable.…”
Section: Resultsmentioning
confidence: 99%
“…This could indicate that not the cytotoxic but the more quiescent CD8 + T-cell subsets are responding to plaque-specific antigens and may be more relevant in the pathogenesis of atherosclerosis. Using experimental mouse models of atherosclerosis it has been shown that the majority of CD8 + T cells in the plaque are antigen-specific, 38 but so far little is known regarding the plaque-antigen(s) they respond to. Whereas CD4 + T cells have been shown to respond to (ox)LDL ([oxidized] low-density lipoprotein) and its related apo B 100 peptide, plaque-antigen(s) for CD8 + remain mostly indefinable.…”
Section: Resultsmentioning
confidence: 99%
“…Naive CD8+ T cells can be differentiated into different subsets with diverse immune functions. 26 It has been previously reported that CD8+ regulatory T cells, which produce predominantly anti-inflammatory cytokines like IL-10, can be generated from circulating naive CD8+ T cells of healthy donors 27 or identified in the heart, spleen, and circulating blood of rats after myocardial infarction, 28,29 as well as in livers of patients with chronic hepatitis C virus infection. 30 In this study, the human CD248+CD8+ T cells also exhibited immune regulatory potential, because they express IL-10 but not IL-1β/INF-γ.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent report has shed light on this issue and on the involvement of CD39 ectonucleotidase in conferring a regulatory and atheroprotective phenotype to CD8 + cells. This is associated with a reduction in cytokine production through increased CD39 expression in both mouse and human atherosclerotic lesions ( 132 ).…”
Section: Modulation Of T Lymphocytes By Purinergic Signaling During Amentioning
confidence: 99%